1997
DOI: 10.1002/(sici)1096-9861(19970210)378:2<205::aid-cne5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal ascending pathways in amphibians: Cells of origin and main targets

Abstract: As part of a research program on the evolution of somatosensory systems in vertebrates, the various components of ascending spinal projections were studied with in vivo and in vitro tract-tracing techniques in representative species of amphibians (the large green frog, Rana perezi, the clawed toad, Xenopus laevis and the ribbed newt, Pleurodeles waltl). Three main ascending sensory channels, each with largely separate targets, were demonstrated: 1. Ascending projections via the dorsal funiculus include primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 105 publications
(195 reference statements)
3
26
0
Order By: Relevance
“…Moreover, in mammals dopamine is involved in the sensory transmission by means of cells in the dorsal horn that project to the dorsal column nucleus (DCN), but not by means of cells that give rise to the spinocervical tract (Doyle and Maxwell, 1993;Doyle, 1994). A similar condition may exist in amphibians, although double-labeling studies are needed to distinguish between the CA innervation of cells that project to the DCN and those constituting the origin of the spinocervical tract (Muñ oz et al, 1995(Muñ oz et al, , 1996(Muñ oz et al, , 1997.…”
Section: Comparison With Other Vertebratesmentioning
confidence: 99%
“…Moreover, in mammals dopamine is involved in the sensory transmission by means of cells in the dorsal horn that project to the dorsal column nucleus (DCN), but not by means of cells that give rise to the spinocervical tract (Doyle and Maxwell, 1993;Doyle, 1994). A similar condition may exist in amphibians, although double-labeling studies are needed to distinguish between the CA innervation of cells that project to the DCN and those constituting the origin of the spinocervical tract (Muñ oz et al, 1995(Muñ oz et al, , 1996(Muñ oz et al, , 1997.…”
Section: Comparison With Other Vertebratesmentioning
confidence: 99%
“…Munoz et al 1991, A. Munoz et al 1995 studies demonstrated rather extensive, somatotopically arranged, spinal afferents to the dorsal column nucleus. The dorsal funicular projection continues rostrally to innervate the vestibular nuclear complex as well as the granular layer of the cerebellum Szekely et al 1980;A. 19.7.4) consists of medial ('gracile') and lateral ('cuneate') compartments.…”
Section: Ascending Spinal Pathwaysmentioning
confidence: 99%
“…The dorsal funicular projection continues rostrally to innervate the vestibular nuclear complex as well as the granular layer of the cerebellum Szekely et al 1980;A. Munoz et al 1997). Fibres terminating in the vestibular region and in the cerebellum (Ebbesson's dorsal spinocerebellar pathway) arise from limbinnervating spinal ganglia Gonzalez et al 1984).…”
Section: Ascending Spinal Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…A single study found that electrical stimulation of the sciatic nerve produces evoked potentials in posterior thalamic nuclei and primordial hippocampal structures in frogs 35. However, the general sensory tracts from spinal neurons make direct connections with neuron groups farther towards the front of the brain as the phylogeny of vertebrates is ascended 36. Throughout phylogeny, all the target sites of spinal tracts in the brain increase in complexity, specialization, and number of neurons, suggesting that even nociceptive messages to the thalamus in an amphibian and mammal may not be similar.…”
Section: Nociception and Pain In Amphibiansmentioning
confidence: 99%